Implementasi Pembelajaran Kooperatif Tipe Team Games Tournament (TGT) untuk Meningkatkan Hasil Belajar Mata Pelajaran Ilmu Pengetahuan Sosial (IPS) pada Siswa Kelas V SDN 2 Talang, Bandar Lampung - Resnawati Resnawati (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2021)
Based on the results of observations through pre-cycle activities by giving formative tests to class V at SDN 2 Talang Teluk Betung Selatan Bandar Lampung after previously providing material through the lecture method, it was found that the level of student learning completeness was 46.9%, which means there were only 15 students out of 32. students who have completed learning and 17 students who have not. After the teacher carried out the reflection, it was found that the teacher had not used innovative and creative approaches, methods, or learning models. This causes students to be less enthusiastic about social studies learning, especially in the Struggle against Invaders material because they are only passive learning objects and only do the tasks given by the teacher. To improve this, the Team Games Tournamet (TGT) type of cooperative learning model was chosen. This research is classroom action research which consists of 2 cycles, each cycle consists of 3 meetings. The research subjects were teachers (researchers) and fifth grade students at SDN 2 Talang Teluk Betung Selatan Bandar Lampung with a total of 32 students. As an observer, the researcher's colleagues were chosen. The variable of this research is Learning Outcomes. Data were collected using test and non-test techniques. Data analysis used quantitative and qualitative descriptive analysis. The results showed that the quality of social studies learning material for Struggle Against Invaders KPK and FPB material through the application of the Team Game Tournament (TGT) type cooperative learning model in class V SDN 2 Talang Teluk Betung Selatan Bandar Lampung has increased. The suggestion from the researcher is that research on the Team Games Tournament (TGT) type of cooperative learning model should not stop here, but can be forwarded to future research in order to obtain more accurate results regarding the Team Games Tournament (TGT) type of cooperative learning model.